1985
DOI: 10.1021/bi00335a026
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline antibiotic reduction by spinach ferredoxin-NADP+ reductase and ferredoxin

Abstract: Spinach NADPH:ferredoxin oxidoreductase (EC 1.6.7.1) catalyzes the NADPH-dependent reduction of the anthracyclines daunomycin, aclacinomycin A, and nogalamycin and their respective 7-deoxyanthracyclinones. Under anaerobic conditions, the endogenous rate of O2 reduction by NADPH catalyzed by ferredoxin reductase (0.12 s-1 at pH 7.4) is augmented by the anthracyclines and 7-deoxyanthracyclinones. The catalytic constants are approximately equivalent for this augmentation for all substrates (approximate V of 2 s-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 49 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…Reductive activation of adriamycin did not yield any transcriptional blockages in addition to those observed under non-reducing conditions, even though the adriamycin was clearly being reduced, as shown by an increasing amount of adriamycinone precipitating from the reaction [26]. The reason that adducts previously observed by others under reducing conditions [12,13] were not observed in the transcriptional analysis is presumably due to the 1000-fold lower DNA con-centration employed in the present work which is based on nanomolar levels of promoter-containing DNA fragments.…”
Section: Adriamycinmentioning
confidence: 77%
“…Reductive activation of adriamycin did not yield any transcriptional blockages in addition to those observed under non-reducing conditions, even though the adriamycin was clearly being reduced, as shown by an increasing amount of adriamycinone precipitating from the reaction [26]. The reason that adducts previously observed by others under reducing conditions [12,13] were not observed in the transcriptional analysis is presumably due to the 1000-fold lower DNA con-centration employed in the present work which is based on nanomolar levels of promoter-containing DNA fragments.…”
Section: Adriamycinmentioning
confidence: 77%
“…However menogarol, being epimeric at C-7, has the pseudoaxial position available (25). Yet it reacts only somewhat faster than nogalamycin (18). Since within this family leaving group stability does not influence the reaction rate, it must be concluded that stereoelectronics alone is insufficient to account for the slow rate of quinone methide formation within the nogalamycin family.…”
Section: I< 2cmentioning
confidence: 99%
“…This is a uniquely suitable reducing agent for quinone methide production in that it is stable in the absence of an oxidant, a strong and rapid reducing agent in the presence of an oxidant, and possesses complete regiochemistry for quinone reduction over C-13 carbonyl reduction. Daunomycin reduction in aqueous solution is most conveniently done with NAD(P)H as the penultimate reducing agent and an enzyme catalyst, NADP:ferredoxin oxidoreductase from spinach (18), as the ultimate reducing agent. In both cases, spectroscopic examination reveals the essentially immediate formation of the quinone methide from the daunomycin hydroquinone, observing at the X__.…”
Section: I< 2cmentioning
confidence: 99%
See 2 more Smart Citations